Effects of call patterns on the likelihood of contact and of interview in mobile CATI surveys - Vicente, P. (2017)
Despite the acknowledged influence of call patterns on contact and response rates in telephone surveys, this relationship is scarcely investigated in mobile CATI surveys. This paper evaluates the effect of call patterns on the likelihood of making contact and of obtaining an interview in a mobile CATI survey and thus furthers the understanding of the potential of mobile phones as a survey mode. Findings reveal that the likelihood of making contact and of obtaining an interview is not uniform across days of the week or times of the day – Tuesdays and Wednesdays are the worst days to make contact and obtain cooperation; weekends are good for successful callbacks. Additionally, longer time lags between consecutive calls do not favour the likelihood of contact or of interview and it is very difficult to interview mobile phone numbers with a call history with many “voicemail” and “rings but no answer” outcomes.